The Fetish of the Ephemeral, the Praxis of Repetition, and the Logic of the Archive - MÜLLER, Péter P. (Studia Universitatis Babeș-Bolyai Dramatica, 2021)
When the very special nature of performance’s evanescence gets emphasized, it is the logic of the archive that lurks beneath the argument, the logic which opposes the residue with the lost and vanished. For a good part of theater scholars, it is the lost and vanished that is valuable; for the archivist it is always the remainder, haunted forever by what’s lost. This paper shall not offer a theoretical overview of the scholarship on repetition or its philosophical interpretations; instead, it will use the concept exclusively in relation with theater plays, theater art, and more broadly the so-called performance arts, in order to reaffirm the bodily dimension of preservation and archiving the theatrical experience.